Comparison of estimated continuous cardiac output with echocardiography in patients with systolic heart failure - Erkus, Musluhittin E.; Altiparmak, Ibrahim H.; Kucuk, Ahmet; Yalcin, Funda; Demirbag, Recep; Kaya, Zekeriya (International Journal of Research in Medical Sciences, 2016)
Background: Cardiac output (CO) is an important hemodynamic parameter in the management of heart failure. The aim of this study was to compare CO measurements obtained from the bedside monitor specialized for CO measurement, which is known as estimated continuous CO (esCCO), and transthorasic echocardiography (echoCO) in patients with ejection fraction (EF) <40%. Methods: A total of 49 patients (36 male) with EF <40% were studied in this study. CO was measured using esCCO and transthorasic echocardiography (TTE). Measurements of CO were compared using Bland-Altman statistical method. Results: Mean ejection fraction was 27.11 ± 7.31%. Measurements of CO using esCCO and echoCO were found to be different (5.44±1.10 L/min vs. 5.08±1.08 L/min, respectively, p=0.004). CO was higher in esCCO compared to TTE. Bland-Altman analysis showed that the bias between esCCO and echoCO was -0.36 L/min [95% CI: -0.60 – (-0.13)], 95% limits of agreement were ranged from -1.77 to 1.05 L/min, and percentage errors of measurements of CO was 13%. A significant positive correlation was found between esCCO and echoCO (r = 0.785, p< 0.001). Conclusions: esCCO was well correlated with echoCO in patients with low EF. The esCCO may be useful for non-cardiologist such as specialist for anaesthesiology and thorasic disease. Also, it may be used in the patients with HF having poor echocardiographic image quality due to co-morbidities including chronic obstructive pulmonary disease.